Espiritualidade, religiosidade e morbidades em estudantes de medicina: estudo em duas universidades brasileiras - NUNES, Joana Katya Veras Rodrigues Sampaio (2018)
Introduction: Changes in Religiousness / Spirituality (R/S) among undergraduate medical students and their influence on mental health, are poorly evaluated. Objec-tive: To evaluate the influence of R/S, its variations / relation with the levels of depres-sion, anxiety and subjective well-being during medical school and its determinants. Materials and Methods: Cross-sectional, analytical, comparative study with medical students from 1st to 6th year, aged 18 and over. The following variables were used: socio-demographic data, Scale for Assessment of Spirituality in Health Contexts (EAECS), Spiritual Well-Being Scale, Duke Religious Index (DUREL), Subjective Well-Being Scale (SWB), Beck Depression Inventory-II (BDI-II), and Beck Anxiety Inventory (BAI). Chi-Square, Spearman’s Rank Correlation, ANOVA or Kruskal-Wallis and mul-tivariate linear regression were used to evaluate factors associated with outcomes. Results: women prevailed (60.5%), white (45.9%), single students (93.8%), from cap-ital and metropolitan region (65.3%) and alcohol ingestion (80.2%) prevailed, equally distributed among levels: Basic (33.4%), Intermediate (33.3%) and Internship (33.3%). The frequency of depression (18.4%) and anxiety (20.6%), moderate to severe, were significant (p> 0.05). Among Negative Affects, there was a higher frequency of stu-dents with low scores (81.2%) and high scores of Positive Affects (72.7%) and Satis-faction (58.1%). High scores of positive Affects, moderate to high score of Existential Welfare, contributed to the reduction of odds from 50% to 80% of depression among those evaluated. Depression was directly proportional to the increase in Negative Af-fect scores, and inversely to the Existential Welfare and Overall Welfare scores, as well as the increase in anxiety symptoms was directly correlated with the increase in the score of Negative Affects. In logistic regression, anxiety symptoms, high scores of Negative Affects, female gender, predisposed the symptoms of depression. For anxiety, the adjustment showed an increased risk of symptoms for the high score of Neg-ative Affects, symptoms of depression, elevated Intrinsic Religiosity and female gen-der. There was a worsening in the mean R/S scores in the 7th semester, and a wors-ening in depression, anxiety and EAECS scores in the 7th and 12th semesters. Organ-izational Religiosity, Religious Well-Being, beliefs/ optimism/ hope, presented a significant β increase (p <0.05), for the semesters of formation and female gender. Non-Organizational Religiosity, Intrinsic Religiosity, Existential Welfare, and General Well-Being showed significant β (p <0.05) increase for age and gender. Symptoms of anxi-ety was the only variable with increased coefficient of regression β for the female gen-der variable (p <0.05). Conclusion: Negative coping of difficulties encountered by un-dergraduate medical students, reduced positive R/S, and may reveal anxiety risk, es-pecially in 7th and 12th semester students.